(untitled) (Journal of the College of Basic Education, 2025)
This study aims to analyses the impact of economic transformations on the social values and future aspirations of young people (aged 18 to 30) in Iraqi cities, focusing on three cities that represent economic and social diversity: Basra, Amara and Ramadi. The importance of the study stems from highlighting young people, who are the cornerstone of any future development, and understanding how their values and aspirations are shaped in a changing economic environment, especially with the increasing problems of unemployment, limited opportunities, and the repercussions of conflicts. The study sought to achieve several objectives, most notably identifying differences in the social values of young people between different cities based on their economic reality, exploring the relationship between economic conditions and levels of youth participation in public life, and analyzing their future aspirations towards migration and entrepreneurship. The study reached key conclusions confirming that economic status is a major determinant of young people’s social values and aspirations. The results showed that young people in relatively economically stable cities (such as Basra) tend to value self-reliance, entrepreneurship, and active community participation more, and are more optimistic about their future within their cities. In contrast, young people in cities facing economic challenges (such as Amara and Ramadi) tend to prefer government job security, increased reliance on family support, and a greater desire to migrate as a means of achieving their ambitions. The results also revealed a strong correlation between lower average income and fewer job opportunities in the private sector, and increased despair and declining confidence in the ability to bring about positive change at the local level. These findings underscore the need for comprehensive and sustainable development policies that take into account the local characteristics of each city and focus on the economic and social empowerment of young people to ensure a better future for Iraq.